Paul, rhetorically gifted, or discursively manipulative? - J. Punt (Acta Theologica)
The rhetoric of the Pauline letters has garnered much interest over the years, and regardless of agreement with the positions expressed in the letters, Paul generally received praise for his adept communicative skills of persuasion. Appreciation for his rhetorical craft, however, should not prevent the recognition of Paul’s deft handling of discourse, as if rhetorical skills and discursive goals are disconnected. Using discourse as a broader category than rhetoric, several instances of discourse manipulation, which at times remind us of imperialist discourse, are identified, including kinship language and ethnic stereotyping, military metaphors, as well as gendered power discourse and sexual slander, illustrated with examples mostly from Philippians.